LINC01355 Contributes to Malignant Phenotype of Oral Squamous Cell Carcinoma and Cytotoxic T Cell Infiltration via Activating Notch Signaling Pathway - Chen Zou; Siyuan Wu; Haigang Wei; Hailing Luo; Zhe Tang; Xia Li; Xiaozhi Lv; Yilong Ai (Journal of Immunology Research)
LINC01355 has been demonstrated to be dysregulated in several cancers. However, the exact molecular function of LINC01355 in the pathogenesis of OSCC remains unstudied. Here, we reported the effect of LINC01355 in OSCC and investigated the mechanisms. Firstly, we found that the results indicated LINC01355 was increased in OSCC cells. Knockdown of LINC01355 repressed OSCC cell proliferation, migration, and invasion. Recently, immunotherapy is a significant method for the treatment of cancers, in which CD8+ T cells exhibit a significant role. The influence of LINC01355 on the antitumor activity of CD8+ T cells was also focused in this study. As shown, the silence of LINC01355 could repress OSCC tumor growth via inducing CD8+ T cell immune responses. In addition, we found that downregulation of LINC01355 significantly restrained CD8+ T cell apoptosis, induced CD8+ T cell percentage, and enhanced the cytolysis activity when cocultured with OSCC cells. It has been reported that the Notch pathway represses CD8+ T cell activity in cancer patients. In our present study, we displayed that lack of LINC01355 suppressed OSCC malignant behaviors and enhanced the antitumor activity of CD8+ T cells via inactivating Notch signaling. We showed that decreased LINC01355 significantly restrained the Notch signal via a decrease of Notch-1, JAG-1, and HES-1. Repression of Notch1 reversed the effect of LINC01355 in OSCC cells. In conclusion, it was implied that LINC01355 might induce the development of OSCC via modulating the Notch signal pathway, which could provide a candidate therapeutic target for OSCC.